Bone mineral density of Bangladeshi people (Daffodil International University Journal of Science and Technology, 2010)
This work is aimed to know about bone mineral density and its influence on bone health. For a preliminary study 30 patients of Nuclear Medicine Centre at Comilla, Bangladesh were chosen. After thorough physical observation and medical examination, their bone mineral density (BMD) and bone mineral content (BMC) at different sites were measured using Dual Energy X-ray Absorptiometer (DEXA). Correlations between BMD and BMC values at different sites of the skeleton were studied. A large incidence of reduced bone mass has been observed. The BMD results for lumber spine (L2-L4) showed a variation with age presenting a distribution, somewhat like an exponential curve. Correlation coefficients suggest that measurement at any site of the skeleton is a competent predictor of fracture at all sites. In addition, BMD and BMC scans of 10 volunteers of age group 5 to 25 were obtained through DEXA at Nuclear Medicine Center, Rajshahi. In the distribution. there was an almost steady rise of BMD with age. DOI: 10.3329/diujst.v4i2.4359 Daffodil International University Journal of Science and Technology Vol.4(2) 2009 pp.6-14